Private Provision of Public Goods and Information Diffusion in Social Groups - Kimberley Ann Scharf (Center for Economic Studies and ifo Institute (CESifo), 2013)
We describe a dynamic model of costly information sharing, where private information affecting collective-value actions is transmitted by social proximity. Individuals make voluntary contributions towards the provision of a pure public good, and information transmission about quality of provision is a necessary condition for collective provision to take place in a stationary equilibrium. We show that, unlike in the case of private goods, better informed individuals face positive incentives to incur a cost to share information with their neighbours; and that these incentives are stronger, and provision of the pure public good greater, the smaller are individuals' social neighbourhoods.
Keywords: H10; L30; D60; D70; 330; private provision of public goods; information transmission; social learning